2020
DOI: 10.1111/hsc.13082
|View full text |Cite
|
Sign up to set email alerts
|

Public’s perspectives on guideline‐recommended self‐medication consultations in German community pharmacies

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Counseling deficits were also noted by the 2 most recent national SPM studies: one also for acute diarrhea OTC medications [ 22 ] and the other for oral emergency contraception (EC) OTC medications [ 23 ]. In addition to contrasting national results from surveys of pharmacy staff [ 68 , 69 ] and from a passers-by survey [ 70 ]—although these results are not surprising due to a social desirability bias or a self-report bias—a nonparticipant observation of pharmacy staff of German CPs for cross-indication counseling practices also found deficits [ 69 ]. In any case, with few exceptions [ 71 ], the present results are consistent with those of international SPM studies for headache medications [ 72 75 ] and for specific analgesics [ 28 , 35 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counseling deficits were also noted by the 2 most recent national SPM studies: one also for acute diarrhea OTC medications [ 22 ] and the other for oral emergency contraception (EC) OTC medications [ 23 ]. In addition to contrasting national results from surveys of pharmacy staff [ 68 , 69 ] and from a passers-by survey [ 70 ]—although these results are not surprising due to a social desirability bias or a self-report bias—a nonparticipant observation of pharmacy staff of German CPs for cross-indication counseling practices also found deficits [ 69 ]. In any case, with few exceptions [ 71 ], the present results are consistent with those of international SPM studies for headache medications [ 72 75 ] and for specific analgesics [ 28 , 35 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, the majority of pharmacy staff stated that most customers—sometimes due to time constraints or preexisting knowledge about the medication—do not want counseling or have already been informed by the physician or in the hospital [ 68 , 69 ]. However, a recent passers-by survey found that most respondents wanted counseling, even if they did not ask for it directly [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of real-world usage of OTC medicinal products by community pharmacists would be useful to set up appropriate guidelines on the management and tri-age of patients suffering from upper GI symptoms, to improve pharmacovigilance, and the establishment of proper counseling on such medicinal products. Considering that patients expect high-quality counseling on self-medication (Seiberth et al 2021;Veiga et al 2021), the use of evidence-based tools for supporting pharmacists is widely recognized as a key point for improving self-medication care (Moritz et al 2019(Moritz et al , 2021a. At the international level, there are many examples of tools accessible to pharmacists (i.e., algorithms or symptom assessment questionnaires) for these disorders (New Zealand Guidelines Group 2003;Aradottir and Kinnear 2008;Holtmann et al 2011;Tack et al 2014;Showande and Adelakun 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the different methods of data collection in the two study parts, a statistical comparison of the results was not applicable. The patients’ perception was not targeted in this study but has already been evaluated by our research group [ 73 ].…”
Section: Discussionmentioning
confidence: 99%